MENINGOENCEPHALITIS IN BROILER CHICKS DUE TO ASPERGILLUS FUMIGATUS INFECTION - AL-Hyali, H. M. I. (The Iraqi Journal of Veterinary Medicine, 2021)
Forty five cases, 7-14 day-old chicks were studied, they showed respiratory and nervous signs with yellowish granulomatous necrotic foci on the air sacs, liver, kidneys, cerebellum and cerebrum. Swabs were taken 7 days post inoculation, culture was made on Sabouraud's dextros agar,. Aspergillus fumigatus was isolated. Diagnosis was confirmed by experimentally exposed one day-old chicks to aerosols of A. fumigatus conidia and also by microscopic demonstration of typical fruiting bodies and spores of the fungus in fresh preparations made from Sabouraud's agar. tissues from fungal-infected Examination of histological sections of cerebrum and cerebellum chicks stained with hematoxylin and eosin and PAS stains revealed granulomas lesion with a central area of necrosis containing heterophils surrounded by macrophages, gaint cells, lymphocytes and layer of fibrous tissue. It was concluded that the cases deal within this study had been infected with A. fumigataus.